Limited Add-On Effects of Unilateral and Bilateral Transcranial Direct Current Stimulation on Visuo-Motor Grip Force Tracking Task Training Outcome in Chronic Stroke. A Randomized Controlled Trial - Taud, Benedikt; Lindenberg, Robert; Darkow, Robert; Wevers, Jasmin; Höfflin, Dorothee; Grittner, Ulrike; Meinzer, Marcus; Flöel, Agnes (Frontiers in Neurology, 2021)
Background: This randomized controlled trial investigated if uni- and bihemispheric transcranial direct current stimulation (tDCS) of the motor cortex can enhance the effects of visuo-motor grip force tracking task training and transfer to clinical assessments of upper extremity motor function. Methods: In a randomized, double-blind, sham-controlled trial, 40 chronic stroke patients underwent 5 days of visuo-motor grip force tracking task training of the paretic hand with either unilateral or bilateral (N = 15/group) or placebo tDCS (N = 10). Immediate and long-term (3 months) effects on training outcome and motor recovery (Upper Extremity Fugl-Meyer, UE-FM, Wolf Motor Function Test, and WMFT) were investigated. Results: Trained task performance significantly improved independently of tDCS in a curvilinear fashion. In the anodal stimulation group UE-FM scores were higher than in the sham group at day 5 (adjusted mean difference: 2.6, 95%CI: 0.6–4.5, p = 0.010) and at 3 months follow up (adjusted mean difference: 2.8, 95%CI: 0.8–4.7, p = 0.006). Neither training alone, nor the combination of training and tDCS improved WMFT performance. Conclusions: Visuo-motor grip force tracking task training can facilitate recovery of upper extremity function. Only minimal add-on effects of anodal but not dual tDCS were observed. Clinical Trial Registration:https://clinicaltrials.gov/ct2/results?recrs=&cond=&term=NCT01969097&cntry=&state=&city=&dist=, identifier: NCT01969097, retrospectively registered on 25/10/2013.